Forecast and interactions of the brazilian cellulose prices in the internal and external markets - Reichert, Bianca (2020)
The production and export of cellulose are important components of the Brazilian economy. The aim of this research was to predict the domestic and foreign prices of the Brazilian cellulose and to evaluate the interference between its average price sold at wholesale and exported by Brazil. The study focused on data from the Forestry Newsletter of the Center for Advanced Studies on Applied Economics (CEPEA), collected from June 2008 to March 2018. The Autoregressive Integrated Moving Average (ARIMA) models were used to predict the wholesale and export price of cellulose, while the Vector Autoregressive (VAR) model was applied to analyze the inter-relation of these variables. It was observed that the price of wholesale and exported celluloses vary in similar periods, due to the direct relationship with the dollar quotation and with the financial crises in the importing countries. The most accurate model adjusted to predict the wholesale cellulose price was the ARIMA model (1,1,0), while ARFIMAX model (1, d*, 0) obtained the best performance to predict exported cellulose price. Based on the VAR model, there was a correlation between variables, which means that wholesale cellulose price has a strong impact on exported cellulose price. Thus, the methodologies used were effective to predict and analyze the inter-relationships between the variables.